Productivity and profitability of rapeseed as influenced by irrigation depth and irrigation scheduling based on can-evaporimeter - Krishna Bharadwaj; K Pathak (Journal of Oilseed Brassica, 2026)
The effects of irrigation depth and irrigation scheduling on productivity and profitability of rapeseed was studied duringRabi 2018-19. Nine treatment combinations of three irrigation depths viz., 4 cm (I1), 5 cm (I2) and 6 cm (I3) and threeirrigation schedules viz., irrigation at 4 cm (D1), 5 cm (D2) and 6 cm (D3) evaporation from a can-evaporimeter were laid outin factorial randomised block design with three replications. Irrigation of 6 cm depth recorded the highest values ofgrowth parameters like plant height, total dry matter accumulation, leaf area index and yield attributing characters viz.number of branches per plant, number of siliquae per plant and number of seeds per siliqua which is, in turn, resulted inhigher seed and stover yields as well. Similarly, irrigation scheduled at 4 cm evaporation from can-evaporimeter resultedin highest yield attributing characters, seed yield and stover yield. Among the different treatment combinations, irrigationof 6 cm depth scheduled at 4 cm evaporation (I3D1) recorded the maximum seed and stover yields, gross returns (Rs.41510/ha), net returns (Rs. 14322/ha) and B:C ratio (1.53).